THE TREND AND VARIATION OF INTELLECTUAL CAPITAL DISCLOSURE AT BANK INDUSTRIES IN EUROPE - Ascaryan Rafinda; Bambang Agus Pramuka; Poppy Dian Indira Kusuma (Universitas Hayam Wuruk Perbanas, 2013)
This study attempts to identify trend on the volume of Intellectual Capital (IC) disclosure, and measurevariation on the volume of IC disclosure on the annual report of banks that operate in Europe. It usespurposive sampling method, consisting of 6 banks with highest rank of market value in different countriesin Europe. The sample includes BNP Paribas (France), Banco Santander (Spain), Intesa Sanpaolo(Italy), UBS (Switzerland), Deutsche Bank (Germany), and ING Group (Netherlands). Data were analyzedusing trend least square to identify the trend of IC disclosure. ANOVA test was employed to measurethe differences in the volume of IC disclosure among banks. The result of this study revealed that 5of 6 banks show positive trends on the volume of IC disclosure. The result also showed that there arevariations on external and human capital disclosure among 6 banks while otherwise for internal capitaldisclosure. The result implied that a global standard which is principle-based in nature cause variationsin the IC disclosures in European Banks. It suggests that the regulator should set standard for voluntaryreporting to minimize the variation on the format and content of the report and to eventually diminishasymmetry information between agent and principal.